Investigating the Effect of Inflation on Economic Growth in Developing Countries: Evidence from Cointegration and VECM Analysis - Hossain, Iqbal; Akter, Rubina; Miah, Sojon (Archives of Business Research, 2025)
The correlation between price increases and economic development has garnered significant attention due to its policy implications, especially in emerging nations. Bangladesh continues to tackle inflation while striving for economic advancement. This study examines the relationship between inflation and economic growth in Bangladesh by employing vector error correction models (VECM) and Johansen's cointegration to analyse both immediate and long-term trends. Each of the time series data previously provided is not stationary at level I (0) but stable at initial difference I (1), according to the unit root test. The ADF test findings demonstrate that the variables are cointegrated at the 1%, 5%, and 10% significance thresholds. A one per cent rise in inflation is linked to a 0.61% increase in economic growth, according to Johansen's cointegration test, which showed a long-term association between the two variables. A one-per-cent rise in the inflation rate will result in a 0.11% decline in the rate of economic growth in the short term. The primary consequence of this premise is that a sudden rise in the price level, regardless of its duration, may hinder economic growth by creating uncertainty, reducing consumer purchasing power, and discouraging investment. The VAR stability criterion demonstrates that all root moduli are inferior to one and lie within the unit circle. The study further indicates the lack of serial correlation at a lag of one. The model estimations are coherent and reliable.